Multicenter evaluation of the updated and extended API (RAPID) Coryne database 2.0. - Funke, G (1997)
In a multicenter study, 407 strains of coryneform bacteria were tested with the updated and extended API (RAPID) Coryne system with database 2.0 (bioMérieux, La-Balme-les-Grottes, France) in order to evaluate the system's capability of identifying these bacteria. The design of the system was exactly the same as for the previous API (RAPID) Coryne strip with database 1.0, i.e., the 20 biochemical reactions covered were identical, but database 2.0 included both more taxa and additional differential tests. Three hundred ninety strains tested belonged to the 49 taxa covered by database 2.0, and 17 strains belonged to taxa not covered. Overall, the system correctly identified 90.5% of the strains belonging to taxa included, with additional tests needed for correct identification for 55.1% of all strains tested. Only 5.6% of all strains were not identified, and 3.8% were misidentified. Identification problems were observed in particular for Corynebacterium coyleae, Propionibacterium acnes, and Aureobacterium spp. The numerical profiles and corresponding identification results for the taxa not covered by the new database 2.0 were also given. In comparison to the results from published previous evaluations of the API (RAPID) Coryne database 1.0, more additional tests had to be performed with version 2.0 in order to completely identify the strains. This was the result of current changes in taxonomy and to provide for organisms described since the appearance of version 1.0. We conclude that the new API (RAPID) Coryne system 2.0 is a useful tool for identifying the diverse group of coryneform bacteria encountered in the routine clinical laboratory.